Trustworthiness measurement methodology for e-business - Hussain, Farookh; Chang, Elizabeth; Dillon, Tharam S. (Springer, 2006)
The purpose of the Trustworthiness Measure is to (a) to determine the quality of the Trusted Agents and (b) once the trusting agent has determined and recorded the trustworthiness of the trusted agent or the quality of the trusted agent, the trusting agent can use this determined and recorded quality of the trusted agent when some other agent queries it about the quality of the trusted agent. As can be clearly seen, if the trusting agent has not determined the trustworthiness of the quality of the trusted agent and subsequently recorded it, then it will not be in a position to communicate recommendations about the trusted agent. Unfortunately, in the existing literature there is no methodology for quantifying and expressing the trustworthiness of the trusted agent. In this paper we propose a methodology by that the trusting agent needs to following in order to determine the trustworthiness of the trusted agent. This methodology helps trusted business transactions, virtual collaboration and keeps the service-oriented environment trustworthy as well as helping to provide a transparent and harmonious nature to the distributed, heterogeneous, anonymous, pseudo-anonymous, and non-anonymous e-service networks.